The Influence of De-Escalation Techniques on Reducing Anger Responses in Drug Clients - Sri Endriyani; Marta Pastari; Sri Martini (PT FORMOSA CENDEKIA GLOBAL, 2023)
Drug abuse is a concern because of the various impacts, one of the negative effects psychologically including tension/anxiety, upset and depressed, loss of self-control and unstable emotional state. Risk Violent behavior is a form of angry response that is expressed by making threats, injuring other people and or destroying the environment. Indonesia's national data for 2020, the risk of violent behavior is around 0.8% or 10,000 people. One of the treatments for the risk of violent behavior can be done with verbal de-escalation techniques. Methods: The design used in this study was pre-experimental with a one group pretest posttest design approach. Total population and sample of 27 respondents (1 treatment group) using total sampling technique. In this design, the treatment group was given verbal de-escalation techniques. The treatment group was given an examination before (pre-test) and after (post-test) verbal de-escalation therapy using the PANSS-EC Rating Scale to assess the patient's angry response at the Mitra Mulia Foundation, Banyuasin Regency. Results: Implementation of verbal de-escalation techniques has an effect on reducing angry responses in clients at risk of violent behavior. Conclusion: Actions that can be taken on clients at risk of violent behavior can be in the form of verbal de-escalation techniques.